RESILIENSI TARUNA STP DARI KELUARGA PELAKU UTAMA PERIKANAN - Sri W. Rahmawati; Mira Rizki Wijayani (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
The boarding campus life at the oficial school with the social and academic demands requires students (also called cadets) to have a tough mental. The risk of campus life creates a stressful condition. There are several ways to solve this problem. The way of them is facing the existing problems; adapting to the reality, and overcoming challenges quickly. They who have succeed to overcome the problem, even rising to become a stronger individual; they will ind a better life. These individuals are said to be resilient individuals. This is a qualitative research to the cadets of Sekolah Tinggi Perikanan (STP), which come from the ishing prime actors (pumakan). The purpose of this research is to describe the resiliency dynamics of STP cadets. The subject research consists of four cadets from the two sexes, which have a background of different regional origin, as well as from families of pumakan (the ishing prime actors). The results of the research analysis can be seen in the various stages of resilient subject in facing the problem. Variations occur in resiliency factors. However, in the aspect of optimism and self-eficacy, overall subjects show the positive results. In addition, protective factors also have a signiicant effect. The protective factors are the resource support and positive characteristics of the individual; the social community and the family support. The overall factors strengthen adaptive ways of coping to the problems occurring.